How to Calculate Bibliometric Using VOSviewer with Publish or Perish (Using Scopus Data): Science Education Keywords - Dwi Novia Al Husaeni; Dwi Fitria Al Husaeni (Indonesian Journal of Educational Research and Technology, 2022)
The purpose of this study is to analyze and demonstrate step-by-step bibliometric data analysis using VOSViewer completely and systematically using article data taken from Scopus. A step-by-step analysis is provided to make first-time users easily follow how to use VOSviewers. This research makes it possible to provide easy data analysis by utilizing capture tools and providing analysis of research developments related to science education. The method used in this study is to perform bibliometric analysis to produce various types of visualizations, namely network visualization, overlay visualization, and density visualization. The analysis was carried out by the number of publications obtained related to a predetermined topic of 200 documents with the range of article publication years from 2013 - 2023. As a practical example, we evaluate the analysis of articles that discuss the keywords used for data collection, namely "Science Education". We found that VOSviewer can be used for shock results in 3 forms of visualization.